2012
DOI: 10.1097/aln.0b013e318242ad4f
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of Closed-loop Titration of Propofol and Remifentanil Guided by the Spectral M-Entropy Monitor

Abstract: Background: This randomized controlled trial describes automated coadministration of propofol and remifentanil, guided by M-Entropy analysis of the electroencephalogram. The authors tested the hypothesis that a novel dual-loop controller with an M-Entropy monitor increases time spent within predetermined target entropy ranges. Methods: Patients scheduled for elective surgery were randomly assigned in this single-blind study using a computergenerated list, to either dual-loop control using a proportional-integr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
53
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(53 citation statements)
references
References 47 publications
0
53
0
Order By: Relevance
“…The most commonly used control signal is the Bispectral Index (BIS) [26][40]. Other control signals include an auditory evoked potential index [41], the spectrogram median frequency [24], [42], [43], a wavelet-based index [44] and an entropy measure [45]. Both standard and non-standard control paradigms [24], [27], [35], [41], [45] have been used in these systems with the principal objective being control of unconsciousness [24], [26][32], .…”
Section: Discussionmentioning
confidence: 99%
“…The most commonly used control signal is the Bispectral Index (BIS) [26][40]. Other control signals include an auditory evoked potential index [41], the spectrogram median frequency [24], [42], [43], a wavelet-based index [44] and an entropy measure [45]. Both standard and non-standard control paradigms [24], [27], [35], [41], [45] have been used in these systems with the principal objective being control of unconsciousness [24], [26][32], .…”
Section: Discussionmentioning
confidence: 99%
“…Several prototype closed-loop systems for general anesthesia have been tested in pilot studies [2731, 66, 67, 7073]. Systems developed to date have relied on a variety of computed EEG features, including wavelet coefficients [72], median spectral frequency [74], BIS [27, 28, 7577], and signal entropy [78]. Some of these derived EEG signals have recently come under criticism for being unphysiological and for being unreliable indicators of depth of anesthesia [36, 7981].…”
Section: Discussionmentioning
confidence: 99%
“…Chen and colleagues [ 4 ] used the SSI for guidance of remifentanil administration, which resulted in lower remifentanil consumption, more stable hemodynamics, and a lower incidence of unwanted events. Liu et al [ 18 ] demonstrated that an intraoperative automated control of hypnosis and analgesia guided by M-Entropy analysis with differential sensitivities to hypnosis and analgesia is clinically feasible and more precise than skilled manual control.…”
Section: Discussionmentioning
confidence: 99%